Bioprospeksi Bakteri Yang Berasosiasi Dengan LamunEnhalus acoroidesdan Syringodium isoetifoliumSebagai Penghasil Senyawa Antibakteri - Luthfy AN; Endang Kusdiyantini; Anto Budiharjo (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Bacteria can grow in variety of environments including those associated with marine organisms such as seagrasses, sponge, algae and soft corals. Bacteria association has the ability to produce bioactive compounds that can be used as a defense against pathogens and their hosts by producing secondary metabolites such as antibacteria compounds. This study aimed to asses the potential of bacteria associated with seagrasses Enhalus acoroides and Syringodium isoetifolium. This study was conducted with bacterial isolation from seagrass E. acoroides and S. isoetifolium, characterization of bacterial isolatesin morphology, antibacterial test, and biochemcal activity test. The result obtained four bacterial isolates, two isolates of Syringodium isoetifolium and two isolates of Enhalus acoroides. Two isolates from Syringodium isoetifolium had the largest ability inhibitory zone of inhibtion against the bacteria P. Aeruginosa (5.7mm) and against the bacteria E. coli (6.65mm).Key word : Antibacterial Compound, Seagrass-Associated Bacteria, Vibrio, Enhalus acoroides, Syringodium isoetifolium